2012
DOI: 10.1177/1046496411429600
|View full text |Cite
|
Sign up to set email alerts
|

The Meeting Genre Across Cultures

Abstract: The current study examines cross-cultural differences in norms for meetings. Following Eisenhardt, we used a broad set of conceptual dimensions for analyzing meetings as a genre of organizational communication (Yates & Orlikowski) to guide a within-and cross-case analysis of meetings in two cultures. Our goal was to discover the possible existence of patterns and interpretations within cultures, and contrasts and explanations across cultures. Data from three different data sets were analyzed encompassing a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Finally, the questionnaire was developed and written in German because all participants were from Germany. Although the meeting procedures suggested and evaluated in this study refer to ideals such as promoting openness with opinions, fairness, and democracy, which are often considered society's most valued ideals (Tracy & Dimock, 2004), employees from different cultures might have different expectations of the structure of meetings and the roles of attendees (Köhler, Cramton, & Hinds, 2012). To increase generalizability, further research validating the ZMQ in other cultures would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the questionnaire was developed and written in German because all participants were from Germany. Although the meeting procedures suggested and evaluated in this study refer to ideals such as promoting openness with opinions, fairness, and democracy, which are often considered society's most valued ideals (Tracy & Dimock, 2004), employees from different cultures might have different expectations of the structure of meetings and the roles of attendees (Köhler, Cramton, & Hinds, 2012). To increase generalizability, further research validating the ZMQ in other cultures would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Extrapolating from research on U.S.-American and German meetings, Germans have been described as "eschewing small talk" (Köhler et al 2012, p. 175). Regarding within-meeting processes, findings further showed that Germans engage in little relational talk during meetings (Köhler et al 2012;Lehmann-Willenbrock et al 2014). Anecdotal evidence for the Germans' apparent aversion of small talk is also ubiquitous in online articles (e.g., Houghton 2017), and popular management books frequently describe Germans as efficient and direct talkers whereas Spaniards are said to be more chatty (Lewis 2006).…”
Section: In-group Collectivism and Pre-meeting Small Talkmentioning
confidence: 98%
“…Although German workplace meetings are described as structured and organized, they are typically less hierarchical than assumed (Hedderich 1999). The need to defend formal authority is low in Germany (Köhler and Gölz 2015) and previous research showed that Germans are expected to voice their opinions during meetings and to take on an active role in decision making (Köhler et al 2012; see also Yin 2002). Seen through this lens, we assume that German meeting participants are more likely to speak up with their own opinions and concerns than Spanish meeting participants who are more inclined to promote group cohesion and in-group collectivism.…”
Section: Power Distance and Voice During Meetingsmentioning
confidence: 99%
See 2 more Smart Citations